Synthesis, molecular structure, optical properties and electrical conductivity of zwitterionic ferrocenyldithiophosphonates - Karakus, Mehmet; Aydogdu, Yildirim; Celik, Omer; Kuzucu, Veysel; Ide, Semra; Hey-Hawkins, Evamarie (Wiley-V C H Verlag Gmbh, 2007)
Ferrocenyldithiodiphosphetane [FcPS(mu-S)](2) [Fe = Fe(eta(5)-C5H4)(eta(5)-C5H5) reacts with the aminoethanol derivatives 1-ethyl-3-pyrrolidinol and 2-(piperazin-1-yl)ethanot to give the zwitterionic (O-ethylammonium)ferrocenyldithiophosphonates [FcP(S)S(OC4H7NHEt)] (2) and [FcP(S)S(OC2H4MHC4H8NH)] (3), which were fully characterized by elemental analysis, IR and NMR spectroscopy and mass spectrometry. The optical and electrical properties of 2 and 3 as well as those of the previously reported [FcP(S)S(OC2H4NHEt2)] (1) were studied. A molecular structure determination of I is also reported.
Keywords: zwitterionic ferrocenyldithiophosphonates; optical properties; molecular structure; conductivity